A Comprehensive Systematic Review of Medical And Non Medical Correlates Of Carpal Tunnel Syndrome - Laela Nurrochmah; Dhian Pangestiningrum (International Medical Journal Corp. Ltd, 2025)
Introduction: Carpal Tunnel Syndrome (CTS) is a common entrapment neuropathy with a multifactorial etiology involving medical, occupational, anatomical, and lifestyle factors. Understanding its diverse correlates is crucial for prevention, diagnosis, and management. Methods: A systematic evidence synthesis was conducted. Forty sources were included after screening based on predefined criteria, including established CTS diagnosis, examination of correlates, robust study design, quantitative association measures, adult population, and human studies. Data were extracted on study design, population, CTS definition, correlates examined, measurement methods, association results, and limitations. Results: Medical correlates with strong evidence include diabetes mellitus (OR=1.90), obesity (OR=2.02), rheumatoid arthritis (OR=1.96), and hypothyroidism (ES=1.44). Pregnancy-related CTS is prevalent (31-62%) and often persists postpartum. Non-medical correlates include occupational biomechanical exposures like vibration (OR=5.40) and hand force (OR=4.23), anatomical factors like a square-shaped wrist (OR=4.56), and female sex (OR=9.99). Psychosocial factors such as high job strain (HR=1.86) and low social support (HR=0.54) are also influential. Genetic factors, including variants in SERPINA1, explain approximately 2% of CTS risk. Notable heterogeneity exists for factors like computer use and smoking, largely dependent on study design and comparison groups. Discussion: The synthesis reconciles heterogeneous findings by emphasizing the impact of diagnostic rigor, study design, confounding, and population context. Diabetes and obesity show consistent, mechanistically plausible links. Occupational risks are hierarchical and potent. Discordant findings for hormone replacement therapy (observational vs. RCT) and smoking (cross-sectional vs. longitudinal) highlight the critical role of study design in causal inference. CTS may serve as an early indicator of systemic conditions like cardiac amyloidosis. Conclusion: CTS is a condition with diverse and interconnected correlates. A holistic, multidisciplinary approach to prevention and management is warranted, considering individual medical history, occupational exposure, anatomical predisposition, and psychosocial context. Future research should prioritize longitudinal designs, standardized diagnostic criteria, and exploration of gene-environment interactions.